2019
DOI: 10.1111/jdv.15954
|View full text |Cite
|
Sign up to set email alerts
|

Body dysmorphic disorder in patients with acne: a multicentre study

Abstract: Background and objective Body dysmorphic disorder (BDD) is a mental disorder that is difficult to diagnose, causes a lot of suffering and is more prevalent in dermatology patients than in the general population. Our objective was to screen for possible cases of BDD in patients with acne and to determine the prevalence according to DSM‐IV and DSM‐5 criteria, as well as to analyse the relationship between dermatological and sociodemographic variables. Methods A total of 245 patients diagnosed with acne in 11 der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
3
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 22 publications
(74 reference statements)
1
23
3
3
Order By: Relevance
“…The patient felt strongly that medical interventions for his appearance concerns would dissipate his anxiety about his appearance, but unfortunately the procedures did not improve his BDD symptoms. Persons with BDD are more likely to seek out nonpsychiatric medical treatment such as surgical procedures or dermatologic interventions over psychiatric treatment for BDD 9,10 . The most common complaints in dermatology clinic patients with BDD include acne, nevi, tumors, hair disorders, and scarring 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patient felt strongly that medical interventions for his appearance concerns would dissipate his anxiety about his appearance, but unfortunately the procedures did not improve his BDD symptoms. Persons with BDD are more likely to seek out nonpsychiatric medical treatment such as surgical procedures or dermatologic interventions over psychiatric treatment for BDD 9,10 . The most common complaints in dermatology clinic patients with BDD include acne, nevi, tumors, hair disorders, and scarring 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Persons with BDD are more likely to seek out nonpsychiatric medical treatment such as surgical procedures or dermatologic interventions over psychiatric treatment for BDD 9,10 . The most common complaints in dermatology clinic patients with BDD include acne, nevi, tumors, hair disorders, and scarring 10 . A naturalistic, prospective (n = 200) study showed that patients with BDD received dermatologic (antibiotics, minoxidil, isotretinoin, and dermabrasion) or surgical interventions in 64% of cases 11 .…”
Section: Discussionmentioning
confidence: 99%
“…People are particularly concerned about their faces, and this takes at least 2 hours a day. 44 In a study conducted with patients with severe acne, 13% of cases had obsessive compulsive personality disorder. 45 In patients with body dysmorphic disorder, looking in the mirror is often seen as a compulsion.…”
Section: Av and Other Psychiatric Diseasesmentioning
confidence: 99%
“…In the study using Body Dysmorphic Disorder Questionnaire, this disorder was more common in female patients and patients with inflammatory lesions. People are particularly concerned about their faces, and this takes at least 2 hours a day 44 . In a study conducted with patients with severe acne, 13% of cases had obsessive compulsive personality disorder 45 .…”
Section: Acne and Self Harm/suicidal Thoughtsmentioning
confidence: 99%
“…депрессии) в связи с угревой болезнью [5,6]. Наличие угревой сыпи на видимых участках кожи может вызывать дисморфофобию (представление о мнимом внешнем уродстве) [7].…”
Section: To Cite This Articleunclassified